Legitimation by naturalization in the news: mechanism, techniques and linguistic means - Chadiuk, Mariia (Current issues of Ukrainian linguistics: theory and practice, 2023)
The article analyzes techniques and linguistic means of legitimation by naturalization in the news. It summarizes definitions of naturalization used in scientific works and classifies them into three groups: (1) representation of actions as something typical or "inevitable result of natural characteristics"; (2) omission of an alternative perspective, which makes mentioned one look like common sense; (3) treating naturalization and normalization as synonyms. The research also explains how different academics modify these definitions. Additionally, two main approaches to the relationship between legitimation and naturalization are singled out. Drawing on T. van Leeuwen's monograph (2008), influential for many studies of CDA, this research analyzes naturalization techniques in the popular news articles (during June 2020 – May 2021) published on the25 most visited Ukrainian media. We suggest that naturalization should include not only evaluation, as T. van Leeuwen believes, but also theoretical rationalization. That's because naturalization by explanation, definition, and prediction, which constitute theoretical rationalization, and evaluation have a common basis for legitimation; the difference is only in the chosen linguistic means. The study proves that T. van Leeuwen's framework needs to be clarified since speakers can also use the purpose, abstraction, and analogy for legitimation by naturalization. Besides, the specificity of naturalization – it justifies action by representing the latter as usual and natural, not through relating it with values – enables its unique role in legitimation. Its linguistic means do not have positive or negative connotations, and by using them, speakers try to present their negative acts as neutral and ordinary. This attribute facilitates applying naturalization in response to criticism from the public or opponents. Analyzed data enables us to assert that naturalization is used for this purpose much more often than to justify something new. The research also singles out linguistic means of legitimation by naturalization.
Keywords: legitimation, media text, naturalization, critical discourse analysis, evaluation, analogy.